Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

(6x+2.4):3 /59=2.25:1/3 find x

Sagot :

We will interpret the question as follows:

[tex](6x+2.4)\colon\frac{3}{59}=2.25\colon\frac{1}{3}[/tex]

The symbol, :, denotes the ratio of two quantities. Then, we can rewrite it as follows:

[tex]\frac{(6x+2.4)}{\frac{3}{59}}=\frac{2.25}{\frac{1}{3}}[/tex]

Using proportions, we can multiply the means of the proportions by the extremes of them as follows:

[tex]\frac{1}{3}(6x+2.4)=2.25\cdot\frac{3}{59}[/tex]

We have that:

[tex]2.25=2+\frac{1}{4}=\frac{8+1}{4}=\frac{9}{4}[/tex]

And

[tex]2.4=\frac{24}{10}=\frac{12}{5}[/tex]

Then, we have:

[tex]\frac{1}{3}(6x+2.4)=2.25\cdot\frac{3}{59}\Rightarrow\frac{1}{3}(6x+\frac{12}{5})=\frac{9}{4}\frac{3}{59}[/tex]

We can multiply by 3 to both sides of the equation:

[tex]3\cdot\frac{1}{3}(6x+\frac{12}{5})=3\frac{9}{4}\frac{3}{59}[/tex][tex]6x+\frac{12}{5}=\frac{9}{4}\frac{9}{59}[/tex]

Subtracting 12/5 from both sides of the equation:

[tex]6x+\frac{12}{5}-\frac{12}{5}=\frac{9}{4}\frac{9}{59}-\frac{12}{5}[/tex][tex]6x=\frac{9}{4}\frac{9}{59}-\frac{12}{5}[/tex]

If we multiply both sides by 1/6, we finally have:

[tex]\frac{1}{6}6x=\frac{1}{6}(\frac{9}{4}\frac{9}{59}-\frac{12}{5})[/tex][tex]x=\frac{1}{6}(\frac{9}{4}\frac{9}{59}-\frac{12}{5})=-\frac{809}{2360}\approx$-0.342796610169$[/tex]

In summary, the value for x in fractional and also in decimal form is:

[tex]x==-\frac{809}{2360}\approx$-0.342796610169$[/tex]